Perlindungan Hak Ekonomi Atas Lagu "Nuansa Bening" Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Pratama, Muhamad Rizky; Permata, Rika Ratna; Rafianti, Laina (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
This research originates from a legal dispute involving Keenan Nasution and Rudi Pekerti, the original composers of the song Nuansa Bening, who filed a lawsuit against singer Vidi Aldiano under Case Number 51/Pdt.Sus-HKI/Cipta/2025/PN Niaga Jakarta Pusat. The composers claimed they had not received any royalties for over 16 years, despite the song being performed publicly 31 times without their authorization, and sought compensation of IDR 24,500,000,000 (twenty-four billion five hundred million rupiah). They also requested the seizure of Vidi Aldiano’s property in Cilandak, South Jakarta. This study employs a normative juridical approach, focusing on secondary data through literature review, including primary legal materials (laws and regulations), secondary legal sources (expert opinions), and tertiary references (legal dictionaries and related materials). The research is descriptive-analytical in nature, using normative qualitative data analysis. The findings reveal that based on Law Number 28 of 2014 concerning Copyright, songwriters as copyright holders are entitled to both moral and economic rights, which are legally protected. If those rights are violated, legal protection for the creators can be pursued based on the principles of automatic protection, recognition of moral rights, and the overarching principles of justice and legal certainty.